Comparison of computer-based cognitive stimulation efficacy with and without transcranial direct current stimulation (tDCS) on the quality of life of patients recovered from Covid-19 - Alireza Lotfi; Alireza rajaei; mahdi Nayyeri (مجله علوم روانشناختی)
Background: Post-COVID-19 neurological sequelae may have a long-term negative impact on cognitive functions and quality of life in recovered patients. Cognitive stimulation based on computer tasks combined with transcranial direct current stimulation (tDCS) is a promising approach to address cognitive impairments and consequently improve the quality of life in these individuals. However, research literature on the effectiveness of this combined method has gaps that require further investigation. Aims: This study aimed to compare the impact of cognitive stimulation based on computer tasks with and without transcranial direct current stimulation on the health-related quality of life in recovered COVID-19 patients. Methods: This research was conducted in the form of a semi-experimental pre-test-post-test design with a control group and a one-month follow-up. The sample size of the study consisted of 45 patients recovered from covid-19 in Mashhad city, who were selected by available sampling method and randomly divided into 3 groups of 15 including computerized cognitive stimulation group, computerized cognitive stimulation combined with single-site anodal electrical stimulation (tDCS) and computerized cognitive stimulation with artificial electrical stimulation (Sham). Participants completed the Weir and Sherburne (1992) SF-36 Health-Based Quality of Life Short Form before and after the intervention. Analysis of variance with repeated measurements and SPSS 24 software were used for data analysis. Results: Both methods of cognitive stimulation based on computer tasks alone and in combination with (tDCS) increased the average scores of the quality of life and its subscales in those who recovered from the acute stage of covid-19 (p=0.05)and this increase was stable in the one-month follow-up phase. In addition, there was no significant difference between the effectiveness of the two treatments in improving the quality of life. Conclusion:Computerized cognitive stimulation alone and together with transcranial brain stimulation can lead to improvement of health-related quality of life in those who have recovered from covid-19 disease. This enables us to enhance and update current rehabilitation programs to meet patient needs.